Thalictrum spiristylum (Ranunculaceae), described from northwestern Yunnan, China, is merged with T. atriplex - Zeng, You-Pai; Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2022)
Based on critical observations on both herbarium specimens (including type material) and living plants in the wild, we demonstrate that Thalictrum spiristylum, described from northwestern Yunnan, China, is conspecific with T. atriplex, a Chinese species widely distributed in southwestern Qinghai, western Sichuan, northwestern Yunnan, and southeastern Xizang. We therefore reduce T. spiristylum to the synonymy of T. atriplex. Morphological distinction between T. atriplex and T. uncatum is clarified. Lectotypification is also proposed for T. atriplex.